One novel naphthalene derivative and other constituents with anti-complementary activities from the aerial parts of Dracocephalum moldavica - Jia-Ming Wang; Jin-Feng Sun; Long Jin; Meng-Jie Wang; Yan-Yan Huang; Mei Jin; Wei Zhou; Gao Li (Taylor & Francis, 2022)
One novel naphthalene derivative, 2-octa-2′,4′,6′-atriynenaphthalene (1), together with eighteen known compounds (2–19) were isolated from the aerial parts of Dracocephalum moldavica L. Compounds 2, 8, 10, 13, 15–17 and 19 were obtained from the family Lamiaceae for the first time, and compounds 11 and 18 were firstly identified from the genus of Dracocephalum. All the isolates were evaluated for anti-complementary activities through the classical and alternative pathways, and the targets of the most active compounds on the complement activation cascade were also investigated.
Keywords: Biochemistry; Microbiology; Cell Biology; Pharmacology; Environmental Sciences not elsewhere classified; Chemical Sciences not elsewhere classified; Biological Sciences not elsewhere classified; Infectious Diseases